The Amino Terminus of Bacteriophage λ Integrase Is Involved in Protein-Protein Interactions during Recombination - Jessop, Lea (American Society for Microbiology, 2000)
Bacteriophage lambda integrase (Int) catalyzes at least four site-specific recombination pathways between pairs of attachment (att) sites. Protein-protein contacts between monomers of Int are presumed to be important for these site-specific recombination events for several reasons: Int binds to the att sites cooperatively, catalytic Int mutants can complement each other for strand cleavage, and crystal structures for two other recombinases in the Int family (Cre from phage P1 and Int from Haemophilus influenzae phage HP1) show extensive protein-protein contacts between monomers. We have begun to investigate interactions between Int monomers by three approaches. First, using a genetic assay, we show that regions of protein-protein interactions occur throughout Int, including in the amino-terminal domain. This domain was previously thought to be important only for high-affinity protein-DNA interactions. Second, we have found that an amino-terminal His tag reduces cooperative binding to DNA. This disruption in cooperativity decreases the stable interaction of Int with core sites, where catalysis occurs. Third, using protein-protein cross-linking to investigate the multimerization of Int during recombination, we show that Int predominantly forms dimers, trimers, and tetramers. Moreover, we show that the cysteine at position 25 is present at or near the interface between monomers that is involved in the formation of dimers and tetramers. Our evidence indicates that the amino-terminal domain of Int is involved in protein-protein interactions that are likely to be important for recombination.